Evaluation of milk yield and composition in nomadic yak and yak crosses - GYELTSHEN, T; DORJI, N (The Indian Journal of Animal Sciences, 2014)
Milk yield and composition of yak and hybrids of yak cow cross Goleng bull, and yak bull cross jatsham reared by nomads were investigated. There was no difference in milk yield and milk constituents among populations. However, hybrid of yak-Jatsham cross yields more milk than the yak-goleng cross in all groups. Yak and yak- Jatsham hybrid’s milk contains the highest (9.52%) and the lowest (8.32%) mean fat per cent, respectively. Yak-jatsham hybrid’s milk compositions were the highest in the first parity group except, fat per cent. Yak-jatsham hybrid should be encouraged to herders because of high milk yield and it’s adaptable to lower altitudes.